Functional nucleic acid-based hydrogels for bioanalytical and biomedical applications. (13th January 2016) - Li, Juan; Mo, Liuting; Lu, Chun-Hua; Fu, Ting; Yang, Huang-Hao; Tan, Weihong
Abstract : We survey advances in bioanalytical and biomedical applications of functional nucleic acid-based hydrogels in this review. Abstract : Hydrogels are crosslinked hydrophilic polymers that can absorb a large amount of water. By their hydrophilic, biocompatible and highly tunable nature, hydrogels can be tailored for applications in bioanalysis and biomedicine. Of particular interest are DNA-based hydrogels owing to the unique features of nucleic acids. Since the discovery of the DNA double helical structure, interest in DNA has expanded beyond its genetic role to applications in nanotechnology and materials science. In particular, DNA-based hydrogels present such remarkable features as stability, flexibility, precise programmability, stimuli-responsive DNA conformations, facile synthesis and modification. Moreover, functional nucleic acids (FNAs) have allowed the construction of hydrogels based on aptamers, DNAzymes, i-motif nanostructures, siRNAs and CpG oligodeoxynucleotides to provide additional molecular recognition, catalytic activities and therapeutic potential, making them key players in biological analysis and biomedical applications. To date, a variety of applications have been demonstrated with FNA-based hydrogels, including biosensing, environmental analysis, controlled drug release, cell adhesion and targeted cancer therapy. In this review, we focus on advances in the development of FNA-based hydrogels, which have fully incorporated both the unique features of FNAs and DNA-based hydrogels. We first introduce different strategies for constructing DNA-based hydrogels. Subsequently, various types of FNAs and the most recent developments of FNA-based hydrogels for bioanalytical and biomedical applications are described with some selected examples. Finally, the review provides an insight into the remaining challenges and future perspectives of FNA-based hydrogels.